Сardioprotective agents with biaromatic structure. Part 1. Calcium channel blockers - G. V. Mokrov (LLC "Publisher OKI", 2022)
Cardiovascular diseases (CVD) are widespread and the leading cause of morbidity and mortality worldwide. Drugs for the treatment of CVD have been developed since the beginning of the 20th century. To date, a large number of cardioprotective agents of various classes have been created. Nevertheless, the need for the development and development of new effective and safe drugs for the treatment of cardiovascular diseases remains. Literature data indicate that a huge number of cardioprotective agents of various generations and mechanisms correspond to a single generalized pharmacophore model containing two aromatic nuclei linked by a linear linker. In this regard, we put forward the concept of creating a new generation of cardioprotective drugs with a multi-targeting mechanism of action within the indicated pharmacophore model. This work begins a series of literature reviews devoted to the generalization of currently known compounds with cardioprotective properties in a series of compounds corresponding to the pharmacophore model of linked biaromatic compounds. The first part presented here describes calcium channel blockers with cardioprotective effects.